Athenian Tragedy in Performance : A Guide to Contemporary Studies and Historical Debates - Powers, Melinda (Book collections on Project MUSE., 2014)
"Investigates the methodological problems that arise in some of the latest research on ancient Greek theatre."--Back cover.